Conflict of Love in Anton Chekhov's The Seagull (1895): An Individual Psychological Approach - Chandra, Anggit Prima, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S.,M.Hum (2015)
The study is about how the conflict of love in Constantine Treplieff character is reflected in Anton Chekhov's The Seagull. The aim of this study is to the major's character personality based on the structural elements and the individual psychological perspective by Alfred Adler. In analyzing this play, the writer uses individual psychological approach and qualitative method. This research is using two data sources, namely primary and secondary data. The primary data source is the script of the play itself, while the secondary data is taken from the information needed. The method of data collection in this research is using qualitative method. The analysis of Constantine Treplieff character starts by analyzing his inferior feeling and compensation, striving for superiority, style of life, creative power, social interest, and fictional finalism. Next, writer analysis discusses the conflict of love that occur in Contantine Treplieff character. According to the analysis that has been conducted, the result of this study shows that unrequited love of Treplieff leads to personality alteration. Until the end of the play, he failed to overcome his personal love issues. Despites all of his effort to obtain Nina's affection, Constantine Treplieff is unable to achieve what he truly wants which is to be loved by Nina. He is unable to accept the reality that Nina remains beyond his reach. This frustrates him and then leads him to commit suicide. Keyword: individual psychology, the seagull, conflict of love